KEDUDUKAN IKATAN JUAL BELI DENGAN KUASA MENJUAL SEBAGAI JAMINAN UTANG DI LINGKUNGAN KOPERASI SIMPAN PINJAM - Hugeng, Diana (Magister Kenotariatan Universitas Surabaya, 2019)
Tangible collateral as part of Tangible Law (Hukum Benda) has a nature of close and enforcing (dwingend recht). It is limiting and prohibiting anyone that will make tangible collateral in a form other than what has been stipulated in the prevailing laws. In relation to loan collateral in form of certificate of right over the land, since the effective date of the Law of the Republic of Indonesia No.4 Year 1996 concerning Encumberance Right over the Land and Things Related to the Land, the only allowable loan collateral is in the form of Encumberance Right. This means loan collateral made in form of Agreement on Commitment to Sell and Purchase with Power of Attorney to Sell is against the law, therefore it is legally stated as null and void due to violating the objective requirements on the legality of an agreement as stipulated in Article 1320 of Burgerlijk Wetboek. Agreement on Commitment to Sell and Purchase with Power of Attorney to Sell as loan collateral is not only against the Law of the Republic of Indonesia No.4 Year 1996 concerning Encumberance Right over the Land and Things Related to the Land, but also against the Law of the Republic of Indonesia No.25 Year 1992 concerning Cooperative, due to the objective of cooperative based on Article 44 point 1 of Cooperative Law is to raise funding from and provide lending to the members of respective cooperative, as well as other cooperatives and/or their members. In case a debtor being a new member of the cooperative when he or she applying loan to the cooperative, it is not aligned with the basic objective of cooperative.